Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada Lembaga Wahdah Inspirasi Zakat - Wandi Saputra Yustin; M. Ikhwan Maulana Haeruddin; Uhud Darmawan Natsir; Chalid Imran Musa; Khaidir Syahrul (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the effect of organizational culture and work environment on employee job satisfaction at Wahdah Inspirasi Zakat institution. A strong organizational culture is believed to help positive employee behavior through the values applied by the company. Meanwhile, a conducive work environment plays an important role in creating employee comfort and productivity. The research method used is quantitative with data collection through questionnaires distributed to employees at Wahdah Inspirasi Zakat. The population at Wahdah Inspirasi Zakat amounted to 38 employees with saturated sampling method. The analysis used in this research is validity test, reliability test, classical assumption test, and hypothesis testing. The results of this study indicate that organizational culture and work environment have a positive and significant influence on employee job satisfaction.